Answer:
a=8 b=6
Step-by-step explanation:
Using the Pythagorean theorem, a^2+b^2=c^2, and in this case, a^2+b^2=10^2 = 100
so a^2+b^2=100
8^2+6^2=100
64+36=100 ✔
and since A is longer than B, a=8, b=6
Answer:
Step-by-step explanation:
<u>Carlos made:</u>
<u>Lily made:</u>
<u>Together they made:</u>
- 12C + 35 + 12L = 12(C + L) + 35
Lily is right. We don't know what 120 means in Carlos's equation, he should put 12L for Lily.
Answer
the correct answer should be 109
Step-by-step explanation:
Answer:
(-4, 16)
Step-by-step explanation:
Answer:
Step-by-step explanation:
Integrating each term with respect to x, we get:
x^3 x^2
f(x) = 9--------- + 4------- - 4x + C
3 2
We are told that if x = 0, f(x) = -7, and so C must equal - 7.
The solution is
x^3 x^2
f(x) = 9--------- + 4------- - 4x - 7, or f(x) = 3x^3 + 2x^2 - 4x - 7
3 2